The experiences of inclusive education teachers on factors that influence their well-being: the case of four full-service schools in Johannesburg west district - Kgapana-Sambo, Mokgadi Precious (My University, 2022)
The introduction of inclusive schooling in 2001 in South Africa has brought through significant demands that require systemic changes and adaption to accommodate the need for an inclusive education structure. The continuous changes in the educational ideologies have seen teachers bear the brunt of implementation with little or no change to the support structure to augment the needs of teachers as the ground force of the system. These changes have subjected inclusive education teachers to well-being challenges; stress, anxiety and depression which have become endemic, requiring support and extensive organisational interventions. It was the intention of this study to investigate the factors that inclusive education teachers working in full-service schools in Johannesburg West district perceive to influence their well-being and how they experience these factors are influencing their well-being. This project was embarked on as a qualitative study through a case study design. A sample of 12 inclusive education teachers was drawn using the purposive method of sampling from four full-service schools. An electronic open-ended survey (structured as a written interview) was employed to gather data from the participants with a thematic method employed to examine the data. This research adds to the understanding of the experiences of inclusive education teachers as they adapt to the emerging teaching environment of full-service learning institutions. The results of this undertaking have confirmed that the inclusive education system influences the well-being of inclusive education teachers. Both positive and negative factors were cited by the participants which highlighted the dynamic circumstances of the inclusive approach. The need for access to support from school-based support teams, school managements and a decentralised school-based professional psycho-social service were highlighted as critical to advancing the inclusive education strategy
A dissertation submitted in partial fulfilment of requirements of degree of f Masters of Arts in Social Work in the field of Occupational Social Work to the Faculty of Humanities, University of the Witwatersrand, 2022